Pre-task cultural knowledge preparation and its effects on consecutive interpreting quality: an empirical study among Chinese postgraduates - Sun, Jin (Frontiers in Education, 2025)
Pre-task cultural knowledge preparation is crucial for ensuring the quality of interpreting. This study investigates the relationship between cultural knowledge preparation and the quality of consecutive interpreting, as well as the common methods used for such preparation. An A-B single group experiment was conducted with 30 postgraduates majoring in English interpreting in China, followed by one-on-one interviews with 8 participants. The experimental recordings were analyzed using SPSS, while the interview transcripts were subjected to content analysis. The findings indicate that overall interpreting quality improved after cultural preparation. Specifically, participants demonstrate significantly higher levels of information accuracy and technique usage, though professionalism shows no significant improvement. Participants report that preparation reduces mental stress, enhances speech comprehension, facilitates content anticipation, and allows for better coordination. The most effective method of cultural knowledge preparation involves obtaining relevant materials about the speaker, topics, and schedules from clients. When self-preparation is required, participants prefer bilingual audiovisual materials from authentic sources.